#### Answer

$-i$

#### Work Step by Step

$i^{11}=i^{8}\times i^{3}=(i^{2})^{4}\times i^{3}$
As $i^{3}=-i$ and $i^{2}=-1$,
$(i^{2})^{4}\times i^{3}=(-1)^{4}\times(-i)=1\times-i=-i$.
Therefore, $i^{11}=-i$.

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.